The Darkness in R.K. Narayan’s novel ‘The Dark Room’ (International Journal of Food and Nutritional Sciences, 2022)
R.K. Narayan’s novel The Dark Room (1938) is darkly woven. The darkness binds the whole novel. Every element in the novel - story, plot, theme, characters, description, society, fate, nostalgia, dialogue, irony, style, and Malgudi - contributes to darkness. Everything in the novel is dark. Besides the title, there is “the dark room”, “the dark hall”, “the dark Sarayu”, “the dark moving water”, “A dark hefty man and a woman”, “a dark corner”, “dark shanty”, “the dark shrine”, “this dark temple” and “his dark face”. The novel describes encircling gloom in the heart of Savitri, the leading character. One may feel that Narayan has casually entitled the novel, The Dark Room. But this is the way Narayan titles his novels. There is behind his casualness a design and a purpose. The Dark Room is more than the tragi-comedy. It is almost a tragedy. The tragedy of Savitri lies in her helpless dependence on her husband and her children.